Effects of Adding Murt Volatile Oil (Myrtus Communis) to Japanese Quail Diets on Growth, Feed Consumption, Carcass, Some Blood and Tissue Characteristics in Lipopolysaccharide-Induced Inflammation - Onel, Suleyman Ercument; Alasahan, Sema; Kucukgul, Altug; Isgor, Mehmet Mustafa; Kanat, Özgür; Hark, Betül Dağoğlu (My University, 2022)
This study, it was aimed to determine the effects of murt volatile oil added to the diet on Lipopolysaccharide (LPS) induced inflammation on body weight, feed consumption, feed conversion ratio, slaughter characteristics, some blood and organ parameters in quails. The study groups were formed as follows: control (commercial chick starter feed), M group (commercial chick starter + 200 mg/kg Murt volatile oil), MLPS group (commercial chick starter + 1 mg/kg-17th day and 7.5 mg/kg- 24th day intrabdominal LPS administered group) and LPS (commercial chick starter feed + 1 mg/kg 17th day and 7.5 mg/kg - 24th day intraabdominal LPS administered group). The study, 4 experimental groups consisting of 40 (4x10) quail chicks were formed and the fattening period lasted for 36 days. The study, blood and liver OSI (Oxidative stress index) values were found to be lower in the M and MLPS groups with murt supplementation than in the control groups without murt addition. During the study, the body weight value was determined lower in the groups with Murt added than in the groups without Murt addition. In addition, the feed conversion ratio was significantly better in the M group with murt supplementation between the 5th and 33rd days than in the other groups. Significant differences were determined between the groups in terms of gizzard ratio and chest+back+neck+wing ratio values. In the study, macroscopic and histopathological hyperemia was not observed in the small intestines, there was an increase in cell infiltration in other groups with added murt compared to the control group, and degeneration and necrosis of the epithelium were detected more prominently. In the study, it was determined that the addition of murt to quail compound feed had a positive effect on growth performance, feed consumption and feed efficiency.
Keywords: Oxidative stress; Liver adiposity; Intestinal hyperplasia